(untitled) - Nylander, Jane C. (Hoboken, N.J., 1990)
This new hardcover edition is a unique single-source presentation of the successful Fabrics for Historic Buildings and Wallpapers for Historic Buildings.
Keywords: Textile fabrics,Textile design,Wallpaper,Vải dệt,Thiết kế dệt may; History,History,History,Lịch sử,Lịch sử,Lịch sử